Testing The Antibacterial Activity of Crude Extracts of Tithonia diversifolia Leaves, Flowers, and Roots in Various Solvent Fraction - Indah Tri Susilowati; Hartati Soetjipto; Susanti Pudji Hastuti (EduChemia (Jurnal Kimia dan Pendidikan), 2022)
Medicinal plants are natural sources of effective antimicrobials from natural products. Tithonia diversifolia (Asteraceae) is a conventional herb that can be used for the treatment of malaria, wounds, and other diseases with biological properties such as antioxidant, antimalarial, antidiabetic, antibacterial, and anti-hyperglycemic. Research on Tithonia diversifolia leaf extract as an antibacterial has been widely carried out. However, its use as a natural antibacterial is rarely studied, especially on flowers and roots. This study aimed to test the antibacterial activity of leaf, flower, and root extracts of the Tithonia diversifolia plant in various solvent fractions. The methods used in this research were Antibacterial Testing with Agar Diffusion and Direct Bioautography Methods, while the solvent fractions used were petroleum ether, chloroform, and ethyl acetate. The results showed that the crude extract of Tithonia diversifolia leaves, flowers, and roots for petroleum ether, chloroform, and ethyl acetate fractions contained antibacterial compounds. They could inhibit the growth of E. coli, P. aeruginosa, S. aureus, and B. subtilis bacteria, with inhibitory activity in chloroform fraction, which was better than in petroleum ether and ethyl acetate fractions. The results of the bioautography test showed that the inhibition was good on gram-positive bacteria with the highest number of spots in the chloroform fraction for the crude leaf and flower extract samples.